Bioinspired sonar reflectors as guiding beacons for autonomous navigation - Simon, Ralph; Rupitsch, Stefan; Baumann, Markus; Wu, Huan; Peremans, Herbert; Steckel, Jancc (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Sonar sensors are universally applied in autonomous vehicles such as robots and driverless cars as they are inexpensive, energyefficient, and provide accurate range measurements; however, they have some limitations. Their measurements can lead to ambiguous estimates and echo clutter can hamper target detection. In nature, echolocating bats experience similar problems when searching for food, especially if their food source is close to vegetation, as is the case for gleaning bats and nectar-feeding bats. However, nature has come up with solutions to overcome clutter problems and acoustically guide bats. Several bat-pollinated plants have evolved specially shaped floral parts that act as sonar reflectors, making the plants acoustically conspicuous. Here we show that artificial sonar beacons inspired by floral shapes streamline the navigation efficacy of sonarguided robot systems. We developed floral-inspired reflector forms and demonstrate their functionality in 2 proof-of-principle experiments. First we show that the reflectors are easily recognized among dense clutter, and second we show that it is possible to discern different reflector shapes and use this identification to guide a robot through an unfamiliar environment. Bioinspired sonar reflectors could have a wide range of applications that could significantly advance sonar-guided systems.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Autonomous navigation; Bioinspired sonar; Echolocation; Robotics; Sonar landmarks